Comparative analysis of autonomic nervous system function in patients with postural orthostatic tachycardia syndrome versus a head-up tilt testing-negative cohort - Jing-Xiu Li, MD, PhD; Xin Qiu, MD; Min Gao, MD, PhD (IBRO Neuroscience Reports)
Purpose: Postural orthostatic tachycardia syndrome (POTS) is a heterogeneous collection of disorders that correspond to autonomic dysfunction. Until recently, it was mostly unresolved as a clinical issue. Our study investigated autonomic function in patients with POTS. Methods: The research utilizes both pre-test 24-hour Holter monitoring to evaluate heart rate variability (HRV) and instantaneous HRV during the head-up tilt test (HUTT), aiming to discern differences in autonomic nervous system (ANS) function between patients positively diagnosed with POTS and those exhibiting negative HUTT results. Results: The 24-hour Holter results derived from time-domain methods demonstrated that SDNN, SDANN, SDNN index, rMSSD, pNN50, and TINN were significantly elevated in the POTS positive group compared to the HUTT-negative group. Meanwhile, frequency-domain methods revealed that low-frequency and high-frequency were significantly elevated in the POTS-positive group relative to the HUTT-negative group. However, the analysis of instantaneous time-domain and frequency-domain parameters during HUTT, including SDNN, RMSSD, SDSD, PNN50, VLF, LF, and HF, revealed no statistically significant differences. Conclusion: The findings suggest that pre-HUTT HRV, as assessed by 24-hour Holter monitoring, may provide greater clinical relevance in distinguishing between these groups. The study reveals that patients with POTS demonstrate abnormalities in autonomic regulation, characterized by a decrease in sympathetic activity alongside an increase in parasympathetic activity. The dysregulation of autonomic balance likely contributes to the elevated incidence of syncope and presyncope events observed in patients with POTS.